Kinetic Studies on Carbon Dioxide Capture using Activated Carbon - Rashidi, Nor Adilla (2013)
Global warming and global climatic changes resulted from anthropogenic carbon dioxide (CO2) emissions has become the main issue recently. Since the beginning of industrial revolution, the concentration of CO2 has increased more than 30 % in the atmosphere, and resulted in various catastrophic occurrences. This study focused on the influence of temperature at 25, 50, and 100 oC towards the CO2 adsorption capacity. Maximum CO2 sorption capacity on the synthesized activated carbon is found to be 80 mg CO2 per gram adsorbent. Experimental data is modelled through Lagergren first-order, pseudo-second-order, and intraparticle diffusion model. From the correlation coefficient, it is found that the pseudo-second-order model is well-fitted with the experimental data. In addition, the activation energy is found to be less than 42 kJ/mol, and it is proved that the physical adsorption occurs.